Jokowi’s Maritime Axis: Change and Continuity of Indonesia’s Role in Indo-Pacific - I Gusti Bagus Dharma Agastia; Anak Agung Banyu Perwita (JAS (Journal of ASEAN Studies), 2015)
Indonesia is undergoing transition and soon, a new president will be inaugurated. The new president brings promises of new foreign and defence policy for Indonesia, building upon Indonesia’s prior principles and putting renewed consideration on Indonesia’s geopolitical position in the Indo-Pacific. This paper examines the “maritime axis”, the concept coined by President Joko Widodo and the possible changes in Indonesian foreign and defence policy required as to achieve the maritime axis. In foreign policy, Indonesia is expected to contribute more to the Indian Ocean Rim Association while maintaining its ASEAN centrality. In defence, there is a significant change in Indonesia’s defence outlook from land-based to maritime-based. Also, Indonesia looks towards India as a security partner in securing the Indian Ocean.